Victoria Chick (1936-2023): an eminent post-Keynesian scholar – some retrospective remarks - Olesen, Finn (Brazilian Keynesian Review, 2023)
For most heterodox economists Victoria Chick stands out as one of the most respected and knowledgeable Post-Keynesian scholars. As such, she has for decades been writing on the economics and methodology of Keynes, on trying to take inspiration from him when analysing important macroeconomic problems of modern times and on the importance of adopting an open system approach when analysing such matters. In this short article, the focus is primarily on Victoria Chick´s work on economic methodology. She argued that methodology should be taken seriously - You cannot simple just do economics. You must consider how to do economics.mics.